KAJIAN PEMANFAATAN LIMBAH KULIT PISANG RAJA (Musa paradisiaca var Raja) DALAM PEMBUATAN ES KRIM - Ermawati, Wa Ode (Jurnal Sains dan Teknologi Pangan, 2016)
The purpose of the research was to determine the formulation of ice cream made from the juice of bananas skin, which was most preferred by the panelists, and to determine its nutritional value. The research was conducted at the Laboratory of Food Technology Faculty of Technology and Agricultural Industry Halu Oleo University, Kendari. The experimental model used in this study was a completely randomized design (CRD) with five treatments and four replicates. The treatments applied were: A1 (without banana skin juice), A2 (with 100 g/kg of banana skin juice), A3 (with 125 g/kg of banana skin juice), A4 (with 150 g/kg of banana skin juice) and A5 (with 175 g/kg of banana skin juice). The results showed that the ice cream made with treatment A3 was most preferred by the panelists. The sensory preference (measured in the range values of 1.00 to 5.00) of the A3 ice cream were: 3.09 in colour (rather attractive), 3.47 in aroma (rather attractive), 3.72 in taste (tasty), 3.92  in texture (soft) and 2.70 in  melting speed (rather quickly melted). The nutritional values of the A3 product formulation were: 1.56% protein 16.67% glucose, 4.64% fat and 5.30% dextrine. The ice cream of A3 treatment was melted in  35 minutes 36 seconds per 100 g.  Keyword: Ice cream, formulation, banana skin juice, sensory values, nutritional values.